Analysis of the Effect of Nickel–Chrome Electroplating Time Variations on Coating Thickness and Surface Hardness of ST41 Material - Arjuna, Ifan Sheva; Utama, Firman Yasa; Puspitasari, Dewi; Nugroho, Aji (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
ST41 steel is a low-carbon steel widely used in the industry due to its toughness, but it has low surface hardness, making it less suitable for components subject to friction. To enhance these surface properties, an electroplating process is performed using nickel as the base layer and chromium as the top layer. This study aims to analyze the effect of varying electroplating time on the thickness and hardness of the ST41 steel surface layer. The research method used was an experiment with variations in nickel coating time of 30 minutes, 45 minutes, and 60 minutes at a voltage of 3 V and a temperature of 55 °C. Chrome plating was carried out for 10 seconds at a voltage of 12 V. Layer thickness testing was conducted using a coating thickness gauge, while surface hardness testing was performed using the Vickers method according to ASTM E384 standards with a load of 50 gf. The research results show that the coating thickness increases with longer plating time, from 18.18 µm at 30 minutes to 20.79 µm at 60 minutes. The highest surface hardness value was obtained at a plating time of 45 minutes, reaching 490.4 HV, then decreased at 60 minutes. This indicates that a plating time of 45 minutes is the most optimal condition for producing a nickel–chrome electroplated layer with the highest surface hardness on ST41 steel.